Opening space for equity and justice in resilience: A subjective approach to household resilience assessment. (May 2021) - Ensor, Jonathan E.; Mohan, Taneesha; Forrester, John; Khisa, Utpal Kanti; Karim, Tasnina; Howley, Peter
Highlights: Measuring resilience reifies assumptions by relying on proxy indicators. Assessment needs methods that place epistemic diversity at the centre. We rank resilience based on subjective assessment of distance to threshold. Participatory methods allow high and low resilience groups to narrate experiences. Resilience root causes and distribution revealed through recognition justice focus. Abstract: While resilience has grown to become a well-established goal of policy and practice, assessing resilience remains an outstanding problem. To date, measurement has largely relied on the identification of proxy indicators, inevitably shaping what is measured in ways that reflect underlying assumptions, generalisations and approximations, and raising the question of whose values are being embedded into resilience. These concerns reflect recent interest in the role of recognition justice in resilience, and in particular how marginalisation from meaning-making processes creates the conditions for the inequitable distribution of outcomes in practice. Here, we propose a two stage, subjective approach to resilience assessment, starting with rapid household interviews that invite participants to assess the likely impact of multiple shock and stressor storylines. In a second step, participatory qualitative methods are employed to support inductive investigation of resilience focused on the factors that differentiate those reporting relatively high and low resilience. We illustrate this using fieldwork data from 569 households in Bangladesh. This subjective approach enables households to engage in the production of knowledge about their resilience, revealing two core features of situated heterogeneity: the forms of difference, and the underlying causes. Underlying causes arise from interactions and feedbacks between social, political, economic and institutional conditions that are highly context specific, while significant forms of difference include intra-community and scalar heterogeneity; vulnerability to specific or generalised shocks; and the role of undesirable practices in securing resilience. The results underline the need for resilience to be assessed in relation to local understandings of precarity, and through the expression of senses of justice that inform local conceptions of wellbeing. This means moving beyond positivist approaches and placing epistemic diversity at the centre of resilience assessment, enabling the production of a situated understanding of how and why resilience is differentiated, and offering an analytical starting point from which policy and practice can drive towards equitable resilience.